Aglycone flavonoid brachydin A shows selective cytotoxicity and antitumoral activity in human metastatic prostate (DU145) cancer cells - de Oliveira, Larissa Cristina Bastos; Nunes, Higor Lopes; Ribeiro, Diego Luis; do Nascimento, Jessyane Rodrigues [UNESP]; da Rocha, Cláudia Quintino; de Syllos Cólus, Ilce Mara; Serpeloni, Juliana Mara (Springer Nature, 2021)
In prostate cancer, flavonoids possess a wide variety of anticancer effects, focused on the antioxidant/pro-oxidant activity, inactivation of the androgen receptor, cell cycle arrest, apoptosis induction, metastasis inhibition, among others. This current research investigated the antitumoral in vitro activity of Brachydin A (BrA), a dimeric flavonoid isolated from Fridericia platyphylla, in human castration-resistant prostate cancer DU145. It was compared BrA selective effects in tumor prostate DU145 cells with non-tumor prostate epithelial PNT2 cells. Cell viability experiments (resazurin, neutral red, MTT, and LDH release assays) showed that BrA was sevenfold more cytotoxic to tumor cells than non-tumor prostate cells, with IC50 values of 77.7 µM and 10.7 µM for PNT2 and DU145 cells, respectively. Furthermore, BrA induced necrosis and apoptosis (triple fluorescence staining assay) without interfering with oxidative stress (CM-H2DCFDA) in DU145 cells. Also, BrA (15.36 µM) reduced cell proliferation on clonogenic assay (DU145 cells) but no change in cell number and protein content was observed when cell growth curve assay was used. Wound healing and transwell assays were used for checking the effects of BrA on cell migration and invasion, and BrA impaired these processes in PNT2 (wound healing) and DU145 cells (transwell). Our results inspire further studies to test BrA as a novel chemotherapeutic drug and to evaluate its effects on drug-resistant metastatic cancer cells. Graphic abstract: [Figure not available: see fulltext.]
Keywords: Apoptosis; Chemoprevention; Cytotoxicity; Fridericia platyphylla; Phytochemical; PNT2 cells